Gender Differences in Depression in the General Population of Indonesia: Confounding Effects. (25th June 2021) - Mumang, Andi Agus; Syamsuddin, Saidah; Maria, Ida Leida; Yusuf, Irawan
Abstract : Background . Research findings on gender differences in depression are inconsistent. This study investigated gender and depression in the Indonesian population and considered possible confounding effects. Methods . This was a cross-sectional study. Participants completed the following self-report measures: demographic characteristic questions, the Cultural Orientation Scale, and the Center for Epidemiological Studies Depression Scale. Gender differences in depression were examined using a generalized linear model. Results . After withdrawals, 265 men and 243 women remained. Women and men did not differ in overall scores and four-factor depression symptoms even after adjusting for cultural orientation and demographic confounding factors, except for the depression symptoms "crying, " "cannot get going, " and "people were unfriendly." Gender differences in depression became significant after adjusting for stereotypical symptom variance. Men reported being lonelier than women. Conclusions . Possible confounding effects on the association between gender and depression are methodological issues, cultural orientation transition, and stereotypical symptoms. Low depression scores found for gender may reflect dimension-counterpart coping strategies .